Health literacy among Filipino adults belonging to low-income families and its association with cancer screening utilization a cross-sectional study - Briones, Marla Vina A. (2017.)
Background: Health literacy has been studied in several countries and reports indicate its association with several health outcomes and health service utilization such as cancer screening. However, health literacy (HL) ans its relation to service utilization, including cancer screening has yet to be explored in the Philippines. Breast cancer screening among Filipino women and prostate cancer screening among Fiilipino men have been recommended for adults upon reaching the age of 50 years by the Philippine Cancer Society. This study aimed to determine the health literacy level (limited, sufficient and excellent) of low-income Filipino adults aged 50-70 years and its association with cancer screening utilization. Methods: Cross-sectional study design was employed to determine the association between health literacy and cancer screening utilization. A total of 2036 Filipino adults?1226 women and 810 men?belonging to low-income families were selected from an urban community. Data were collected through face-to-face interview using the HLS-Asia Questionnaire. Results: Majority of the respondents have problematic (68.3%) and inadequate (25.5%) health literacy levels or a combined proportion of 94%. Inadequate health literacy was more common in men, less than high school education, no health insurance, no relative with medical background, and did not visit a doctor in the past year. A significant proportion of respondents reported difficulty in accessing (30-50%), understanding (20-34%), judging (25-50%), and applying (16-44%) health information. Cancer screening utilization, on the other hand, was also found to be low for both men and women. Only 2% of women ever had mammography upon reaching 50 years of age while only 6% of men in the same age group ever had either digital rectal exam (DRE) or prostate-specific antigen (PSA) testing. Among those who never had the said tests done, majority reported that they did not feel the need for the test, having been free of any cancer symptom. After controlling for significant confounders, health literacy was found to be significantly associated with mammography utilization. Furthermore, those with problematic health literacy are about eleven times more likely to undergo mammography as compared to those with inadequate health literacy (OR: 10.63, 95%CI 1.23 ? 91.76). On the contrary, the study did not find sufficient evidence to say that health literacy is associated with prostate cancer screening utilization (OR: 1.17, 95%CI 0.40 ? 3.38). Conclusion: A large proportion of men and women age 50-70 years old have inadequate and problematic health literacy. Although an association between health literacy and mammography utilization was evident, there was no indication that it is associated with prostate cancer screening utilization. Nevertheless, it is important to increase the health literacy level of Filipinos by improving access to health information from healthcare workers and various forms of media. Adult men and women should also be encouraged to undergo cancer screening tests aided with proper information of its importance and usefulness. Lastly, public health campaigns should consider health literacy level especially if the target population are those who belong to low-income families. Further studies are warranted to determine the health literacy of the general population.
Available in CD, pdf copy.
Thesis (Master of Science in Public Health, Epidemiology)--University of the Philippines Manila.
Keywords: Medical screening; Health education; Medical care -- Utilization; Health facilities -- Utilization